2014
DOI: 10.1038/cddis.2014.338
|View full text |Cite
|
Sign up to set email alerts
|

Impaired cell death and mammary gland involution in the absence of Dock1 and Rac1 signaling

Abstract: Throughout life, the tight equilibrium between cell death and the prompt clearance of dead corpses is required to maintain a proper tissue homeostasis and prevent inflammation. Following lactation, mammary gland involution is triggered and results in the death of excessive epithelial cells that are rapidly cleared by phagocytes to ensure that the gland returns to its prepregnant state. Orthologs of Dock1 (dedicator of cytokinesis 1), Elmo and Rac1 (ras-related C3 botulinum toxin substrate 1) in Caenorhabditis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 47 publications
(70 reference statements)
0
31
0
Order By: Relevance
“…In support of the idea that Rac1 function is not essential for mammary gland development, deletion of the Rac1 GEFs Tiam1 or Dock1 also did not significantly affect mammary gland development (15,28). However, Dock1 deletion delayed involution.…”
Section: Rhogefs In Mammary Gland Developmentmentioning
confidence: 57%
See 2 more Smart Citations
“…In support of the idea that Rac1 function is not essential for mammary gland development, deletion of the Rac1 GEFs Tiam1 or Dock1 also did not significantly affect mammary gland development (15,28). However, Dock1 deletion delayed involution.…”
Section: Rhogefs In Mammary Gland Developmentmentioning
confidence: 57%
“…This delay was greater than after Rac1 deletion, perhaps reflecting the ability of Dedicator of cytokinesis 1 (Dock1) to activate Rac3 as well as Rac1. Similar to Rac1 deletion, loss of Dock1 delayed Stat3 activation and prevented epithelial cell apoptosis within the alveoli (15). Because Tiam1 and Dock1 function as GEFs for Rac1 subfamily GTPases, these observations indicate that Rac signaling is mainly important during involution.…”
Section: Rhogefs In Mammary Gland Developmentmentioning
confidence: 82%
See 1 more Smart Citation
“…In fact, it has been reported that Rac1 is required for apoptotic cell clearance in bronchial epithelial cells and cell death in mammary gland epithelium. 18,19 Besides, we found that Rac1 mediates TNFα-induced uterine epithelial apoptosis via P38 MAPK signaling. TNFα has been demonstrated to be essential for epithelial cell apoptosis and it could upregulate the level of Rac1-GTP in intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 78%
“…Because Ras-related C3 botulinum toxin substrate 1 (Rac1), a small GTPase belonging to the 21 kDa Rho-GTPase family, 16,17 is a multifunctional switch involved in epithelial development, differentiation and apoptotic cell clearance in various systems, [18][19][20][21][22] and Rac1 is also involved in regulating human endometrial stromal cell migration in culture, 23 we speculated that Rac1 and its driving signaling cascade might be an important player directing normal luminal epithelial integrity conducive to on-time embryo implantation. To address this issue, in the present study, we used a uterine Rac1 conditional deletion mouse model and demonstrated that Rac1 depletion in the uterus induces premature decrease of epithelial apical-basal polarity and defective junction remodeling, hampering normal uterine receptivity and thus on-time embryo implantation.…”
mentioning
confidence: 99%